La Evolución del Periodismo Deportivo en la Era Digital: Análisis de las Estrategias de Cobertura, Participación de la Audiencia y Nuevos Modelos de Negocio - ALVARADO ALVARADO, PAUL ARIEL (2024)
The objective of this work is to analyze the evolution of sports journalism in the digital era through a detailed analysis of coverage strategies, audience participation and new business models, to identify opportunities for improvement, optimization and adaptation to changes. in the city of Guayaquil through the detailed analysis of journalistic strategies, public involvement and new business models. We used qualitative methods to review previous research and studies and conduct five interviews with local sports journalists working in digital media. This approach provides a clear understanding of the current state of knowledge in the field and the experiences and perspectives of experts in the field. Given the continuous evolution of sports magazines, this research is important to identify opportunities for improvement and adaptation to technological developments and transition strategies towards more efficient digital models. The goal is to provide new insights into the state of digital sports journalism in Guayaquil, influence communication and education professionals, and provide important information and updates on project activity.